Ethical Perspective on Genetic Diseases and Tests - Hayırlıdağ, Mustafa (Aksaray Üniversitesi, 2022)
Genetics is the science that studies the structure and functions of genes and the inheritance of genetic characteristics. The science of genetics originates from the work of Mendel in the mid-19th century. However, many opinions about heredity have been put forward before Mendel. In the modern sense, genetics has been revealed by molecular studies. Today, with the development of technological opportunities, genetic tests have also advanced a lot. In this study, after an overview of genetics and the tests performed, an evaluation was made in terms of ethical principles. Genetic diseases and the tests applied in their diagnosis and their results can create ethical problems in some cases in terms of basic human rights and ethical principles. In these cases, clinical ethics comes into play. An approach that respects the rights of the individual and society is possible only in the light of universal ethical principles and basic ethical guidelines.

Genetik, genlerin yapı ve işlevleriyle genetik özelliklerin kalıtımını inceleyen bilim dalıdır. Genetik bilimi Mendel’in 19. yüzyılın ortalarındaki çalışmalarından köken almaktadır. Ancak Mendel’den önce de kalıtım hakkında birçok görüş ileri sürülmüştür. Modern anlamda genetik ise moleküler bazda yapılan çalışmalarla ortaya çıkarılmıştır. Günümüzde teknolojik imkanların da gelişimiyle yapılmakta olan genetik testler de bir hayli ilerlemiştir. Bu çalışmada, genetik bilimine ve yapılan testlere genel bir bakıştan sonra etik ilkeler açısından değerlendirme yapılmıştır. Genetik hastalıklar ve onların tanısında uygulanan testler ve sonuçları, temel insan hakları ve etik ilkeler açısından bazı durumlarda etik sorunsallar oluşturabilmektedir. Bu durumlarda klinik etik devreye girmektedir. Bireyin ve toplumun haklarını gözeten bir yaklaşım ancak evrensel etik ilkeler ve temel etik rehberler ışığında mümkündür.
Genetik Hastalıklar ve Testlere Etik İlkeler Açısından Bakış
Keywords: Clinical Sciences; Klinik Tıp Bilimleri